Supramodal executive control of attention - Spagna, Alfredo; Mackie, Melissa-Ann; Fan, Jin (Frontiers in Psychology, 2015)
The human attentional system can be subdivided into three functional networks of alerting, orienting, and executive control. Although these networks have been extensively studied in the visuospatial modality, whether the same mechanisms are deployed across different sensory modalities remains unclear. In this study we used the attention network test for visuospatial modality, in addition to two auditory variants with spatial and frequency manipulations to examine cross-modal correlations between network functions. Results showed that among the visual and auditory tasks the effects of executive control, but not effects of alerting and orienting were significantly correlated. These findings suggest that while alerting and orienting functions rely more upon modality specific processes, the executive control of attention coordinates complex behavior via supramodal mechanisms.